Semi-arid hilly area low-disturbance soil preparation rainwater harvesting vegetation recovery method - Yin Zhe; Qin Wei (2016)
The invention relates to a semi-arid hilly area low-disturbance soil preparation rainwater harvesting vegetation recovery method. The method comprises the steps that according to the planting density of vegetation to be planted on a slope, a plurality of soil preparation members comprising arched curved plates are distributed on the slope; an opening of the arched curved plate in each soil preparation member faces the slope in the horizontal direction, and the arched curved plates are exposed out of the earth surface; vegetation is planted within the retaining range of each soil preparation member. As the soil preparation members are utilized for carrying out vegetation recovery on the slope, in the soil preparation process, the excavation and ground breaking work amount is small, the disturbance to the slope is small, and the problem that the formed soil texture platform type or pit-like local terrain structure is unstable is avoided. By the adoption of the recovery method, on the basis of effectively retain